Aging of microplastics promotes their ingestion by marine zooplankton. (December 2017) - Vroom, Renske J.E.; Koelmans, Albert A.; Besseling, Ellen; Halsband, Claudia
Abstract: Microplastics (<5 mm) are ubiquitous in the marine environment and are ingested by zooplankton with possible negative effects on survival, feeding, and fecundity. The majority of laboratory studies has used new and pristine microplastics to test their impacts, while aging processes such as weathering and biofouling alter the characteristics of plastic particles in the marine environment. We investigated zooplankton ingestion of polystyrene beads (15 and 30 μm) and fragments (≤30 μm), and tested the hypothesis that microplastics previously exposed to marine conditions (aged) are ingested at higher rates than pristine microplastics. Polystyrene beads were aged by soaking in natural local seawater for three weeks. Three zooplankton taxa ingested microplastics, excluding the copepod Pseudocalanus spp., but the proportions of individuals ingesting plastic and the number of particles ingested were taxon and life stage specific and dependent on plastic size. All stages of Calanus finmarchicus ingested polystyrene fragments. Aged microbeads were preferred over pristine ones by females of Acartia longiremis as well as juvenile copepodites CV and adults of Calanus finmarchicus . The preference for aged microplastics may be attributed to the formation of a biofilm. Such a coating, made up of natural microbes, may contain similar prey as the copepods feed on in the water column and secrete chemical exudates that aid chemodetection and thus increase the attractiveness of the particles as food items. Much of the ingested plastic was, however, egested within a short time period (2–4 h) and the survival of adult Calanus females was not affected in an 11-day exposure. Negative effects of microplastics ingestion were thus limited. Our findings emphasize, however, that aging plays an important role in the transformation of microplastics at sea and ingestion by grazers, and should thus be considered in future microplastics ingestion studies and estimates of microplastics transfer into the marine food web. Graphical abstract: Highlights: Ingestion of microplastics by marine zooplankton depends on species and life-stage. Both microplastic beads and fragments are ingested. Aging in natural seawater promotes microplastic ingestion. Microplastics do not directly affect the survival of a key copepod species. Abstract : Microplastics aged in natural sea water are more readily ingested by zooplankton than pristine microplastics, irrespective of grazer species or developmental stage. Fragments as well as beads were readily ingested, but egestion of both types occurred within hours, limiting negative effects of polystyrene ingestion on zooplankton physiology and shifting the potential for trophic transfer and biomagnification in marine food webs to the faeces.